Employment Law: Coach-on-Athlete Abuse: Editor: Thomas H. Sawyer. Issue 7 (2nd September 2019) - Sawyer, Tonya L.
Abstract : Devarus Robinson was a player on the Kathleen High School football team in Lakeland, FL. While on the team, Robinson was constantly subjected to bullying and physical abuse by the school's head football coach, Irving Strickland. Robinson sued the Polk County School Board for neglectful hiring and supervision of Coach Strickland.